A navigational role-centric model oriented web approach - MoWebA. (2016) - González, Magalí; Cernuzzi, Luca; Pastor, Oscar
This study presents MoWebA, a navigational role-centric model driven development (MDD) proposal for web applications development. The approach was conceived considering a previous study of web methods and analysing some open issues. This article presents the fundamentals of the proposal; the methodological aspects for modelling and transformation processes; and the defined notations/techniques for modelling and transformation tasks, including their abstract and concrete syntax definitions. We include a summary of the validation experiences and main results, and a comparison against other related proposals, in order to highlight the main contributions of MoWebA.